Cardin's Whitefly, Metaleurodicus cardini (Back) (Insecta: Homoptera: Aleyrodidae: Aleurodicinae) - Avas B. Hamon (EDIS, 2003)
Cardin's whitefly, Metaleurodicus cardini (Back), has been known in Florida since 1917. It was originally described from Cuba and was named for Professor Patricio Cardin. This whitefly is usually innocuous, but under some situations can become a damaging pest. These situations usually occur when something has disrupted the parasite/predator complex. This document is EENY-153 (originally published as DPI Entomology Circular 316), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2000. Revised: December 2003.